Yang-Dan-Tang, Identified from 15 Chinese Herbal Formulae, Inhibits Human Lung Cancer Cell Proliferation via Cell Cycle Arrest. (30th May 2012) - Wang, Tien-Chun; Fang, Chih-Nan; Shen, Chih-Chien; Wei, Hui-Yu; Weng, Yui-Ping; Lin, Jung-Yaw; Hsieh-Li, Hsiu Mei; Lee, Chen-Yu
Abstract : Lung cancer has long been one of the most deadly forms of cancer. The majority of lung cancers are of the non-small-cell lung cancer (NSCLC) type. Here we used the non-small-cell lung carcinoma cell line A549 to screen 15 different traditional Chinese herbal medicine (CHM) formulae to explore the possible mechanisms of alternative medicine in lung cancer therapy. We identified three formulae (Formulae 3, 5, and 14) that substantially decreased the survival of A549 cells but did not affect MRC5 normal lung tissue cells. Formula 14, Yang-Dan-Tang, a modified decoction of Ramulus Cinnamomi Cassiae, was chosen for further characterization. Flow cytometry analysis showed that treatment of Formula 14 induced cell cycle arrest in G1 and G2 phase without causing significant cell death. These results were also confirmed by Western blot analysis, with decreased expression of G1/S and G2/M promoting cell cycle machinery including cyclin D3, cyclin B1, CDK4, and CDK6. This study provides further insight into the possible working mechanism of Yang-Dan-Tang in patients.